Star Wars : shadow games - Reaves, Michael; Bohnhoff, Maya Kaathryn (New York : Del Rey/Ballantine Books, 2011)
When he agrees to be the bodyguard of Javul Charn--the most famous pop star in the galaxy and the runaway bride of a violent lieutenant in Black Sun--Dash Rendar, broke and desperate, must discover who is trying to sabotage Javul's tour and finds an unexpected ally in Han Solo.
'Lucas books.'
Keywords: Solo, Han (Fictitious character) -- Fiction; Bodyguards -- Fiction